Tensile Strength and Density Evaluation of Composites from Waste Cotton Fabrics and High-Density Polyethylene (HDPE): Contributions to the Composite Industry and a Cleaner Environment - Sri Mulyo Bondan Respati; Helmy Purwanto; Ilham Fakhrudin; Pungkas Prayitno (Universitas Muhammadiyah Magelang, 2021)
The growth of the textile industry and the massive use of plastic-based materials create economic growth, but it produces waste from post-use, such as clothing waste from cotton fabrics and HDPE that can be recycled and combined as composite materials. Therefore, an experiment was carried out to investigate and analyze the effect of the fiber volume fraction of waste cotton fabric (1.5%, 3.5%, 4.5%, 6%, and 7.5%) with straight fiber arrangement on the tensile strength and density. From the test results, a tensile strength of 178.4 MPa and 182.6 MPa was obtained for yield and max stress, respectively at a fiber volume fraction of 7.5%. Meanwhile, the highest density of 0.95 g/cm3 was obtained at 1.5% fiber volume fraction. The fracture macroscopic view of the specimen shows a resilience fracture (uneven and appears stringy). Although the strength of this composite cannot yet compete with the new composite material, it has a decent environmental contribution. Considering the availability of waste cotton fabrics and HDPE, it promises to be produced as a low-strength composite for construction, ornamentation, or coatings.